HEPATOPROTECTIVE EFFECTS OF TRIBULUS TERRESTRIS, ASHWAGANDHA AND N-ACETYLCYSTEINE ON LIVER FIBROSIS IN CARBON TETRACHLORIDE-INDUCED RATS - Altay, Derya; Dogan, Yasar; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Şahin, Kazım (Polskie Towarzystwo Farmaceutyczne, 2019)
Fibrosis, which develops during the progression of liver damage, is the previous stage of cirrhosis. Carbon tetrachloride is one of the most commonly used hepatic toxins in experimental animal models of liver fibrosis. It was investigated the hepatoprotective effects of Tribulus terrestris, Ashwagandha and N-acetylcysteine in an experimental model of liver fibrosis induced by carbon tetrachloride in this study. Fifty Wistar rats were divided into live groups of 10 each, as follows: 1) Control, 2) Carbon tetrachloride, 3) Carbon tetrachloride plus N-acetylcysteine, 4) Carbon tetrachloride plus T. terrestris, and 5) Carbon tetrachloride plus Ashwagandha group. At the end of 6 weeks, the rats were sacrificed, and serum and tissue samples were collected. Aspartate arninotransferase, alanine zuninotransferase, gamma-glutamyltranspeptidasc, malondialdehyde. NF-kappa B, collagen 1, nuclear factor erythroid-2-related factor 2, tumor necrosis factor-alpha were analyzed, and histopathological evaluation was performed. There were no significant differences in serum aspartate aminotransferase and alanine aminotransferase levels of the N-acetylcysteine-treated group versus those in the T. terrestris- and Ashwagandha-treated groups (p > 0.05). Liver malondialdehyde levels were lower in the N-acetylcysteine-, T. terrestris- and Ashwagandha-treated groups than in the carbon tetrachloride-administered group (p < 0.001). There were differences between groups in NF-kappa B, collagen 1, nuclear factor erythroid-2-related factor 2 and tumor necrosis factor-alpha levels (p < 0.05). In conclusion. T. terrestris, Ashwagandha and N-acetylcysteine had protective effects on the liver in this experimental fibrosis model. T. terrestris was a little more effective than Ashwagandha in combating liver fibrosis.
Keywords: Ashwagandha; carbon tetrachloride; N-acetylcysteine; Tribulus terrestris; liver fibrosis